Ground reaction forces during running can be estimated from insole pressure measurements by considering whole body dynamics - Chumanov, E. S.; Remy, C. D.; Thelen, D. G. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Insole pressure sensors allow one to gauge the pressure distribution on the foot, in addition to the net center of pressure (COP) and vertical force (Chesnin et al. 2000). However, current insoles do not provide measures of shear force, which means that traditional biomechanical analyses of joint and muscle loads cannot be conducted. Kuo (1998) showed that center of pressure information may be sufficient to estimate shear forces when a least squares inverse dynamics (LSID) approach is used. We have extended these ideas to generate least squares forward dynamic (LSFD) simulations of locomotion that are dynamically consistent over time (Remy et al. 2008). The objective of this study was to evaluate the accuracy of using insole pressure data together with LSFD to estimate ground reactions during running.